2020
DOI: 10.1021/jacs.9b09755
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Block Heterochiral Peptides into Helical Tapes

Abstract: Patterned substitution of d -amino acids into the primary sequences of self-assembling peptides influences molecular-level packing and supramolecular morphology. We report that block heterochiral analogs of the model amphipathic peptide KFE8 (Ac-FKFEFKFE-NH 2 ), composed of two FKFE repeat motifs with opposite chirality, assemble into helical tapes with dimensions greatly exceeding those of their fibrillar homochiral counterparts. At sufficient concentrations, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 27 publications
5
61
0
Order By: Relevance
“…In terms of structure, most studies focus on the effects of chirality alteration on the morphology, size, and secondary structure of peptide assemblies, while the molecular mechanisms for these effects are relatively less explored. It is worth noting that many researchers have combined Molecular Dynamics (MD) calculations with experimental data and successfully elucidated the molecular basis for the changes in the assembly structures of peptides caused by chirality conversion ( Wang M. et al, 2017 ; Clover et al, 2020 ). Therefore, the combination of computational approaches and an arsenal of experimental techniques is supposed to be a useful tool to undercover the chirality effects in peptide assemblies on the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of structure, most studies focus on the effects of chirality alteration on the morphology, size, and secondary structure of peptide assemblies, while the molecular mechanisms for these effects are relatively less explored. It is worth noting that many researchers have combined Molecular Dynamics (MD) calculations with experimental data and successfully elucidated the molecular basis for the changes in the assembly structures of peptides caused by chirality conversion ( Wang M. et al, 2017 ; Clover et al, 2020 ). Therefore, the combination of computational approaches and an arsenal of experimental techniques is supposed to be a useful tool to undercover the chirality effects in peptide assemblies on the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that replacing one Phe of FF with its D -enantiomer preserved its ability to self-assemble into nanotubes and the heterochirality made the nanotubes more homogeneous and stable ( Kralj et al, 2020 ), while switching the chirality of one Phe of FF derivatives, such as Fmoc-FF-Fmoc and Nap-FF, changed the morphology of their assembly structures ( McAulay et al, 2019 ; Gil et al, 2020 ). The Rudra group explored the effects of multiple and consecutive amino acid chiral mutations on the assembly structure of peptide Ac-(FKFE) 2 -NH 2 ( Clover et al, 2020 ). The results showed that the heterochiral analogs of the model peptide, composed of two FKFE repeat motifs with opposite chirality, self-assembled into helical tapes with a width of 108 ± 55 nm and a pitch of 900–1200 nm.…”
Section: Manuscript Formattingmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Heterochirality is gaining momentum as a strategy to tailor peptide self-assembly. 34 36 Uncapped dipeptides are very attractive building blocks due to their chemical simplicity. Furthermore, enantiomers are expected to display the same self-assembly behavior in achiral environments, therefore, investigation of compounds 2 – 6 will shed light also on the self-assembly of their mirror-image l - d dipeptide isomers.…”
mentioning
confidence: 99%
“…Highly ordered and solid‐state porous two‐dimensional (2D) nanomaterials are a new class of materials (Karak et al, 2017; Karak, Kumar, Pachfule, & Banerjee, 2018; Zhang et al, 2019), that have shown wide‐spread applications in catalysis (Chen, Zhang, Jiao, & Jiang, 2018), sensing (Das et al, 2015; Ding et al, 2016; Ma et al, 2018), biomedical (Fang, Kim, Kim, & Yu, 2013; Yang, Léonard, Lemaire, Tian, & Su, 2011), gas adsorption (Ma et al, 2018; Zhu et al, 2017), and energy storage (Kou et al, 2017). These 2D nanomaterials include graphitic carbon nitride (g‐C 3 N 4 ) (Wang, Zhang, Li, Li, & Wu, 2017; Zhang et al, 2013), transition metal dichalcogenides (TMDs; Carrow et al, 2020; Jaiswal, Singh, Lokhande, & Gaharwar, 2019; Lu, Yu, Ma, Chen, & Zhang, 2016; Zhang, Lai, Ma, & Zhang, 2018), covalent organic frameworks (COFs; Bhunia, Deo, & Gaharwar, 2020), hexagonal boron nitride (h‐BN; Deshmukh, Jeong, Lee, Park, & Kim, 2019; He et al, 2019), layered double hydroxides (LDHs; Yu, Wang, O'Hare, & Sun, 2017; Zhao et al, 2017), layered silicates (nanoclay) (Gaharwar et al, 2019), polymer sheets (Clover et al, 2020), and noble metal nanosheets (Huang et al, 2011; Sancho‐Albero et al, 2019). Diverse biomedical applications of these nanomaterials are owing to their versatile properties including high surface area, high conductivity, and superior optical properties (Brokesh & Gaharwar, 2020; Chimene, Alge, & Gaharwar, 2015; Gaharwar, Singh, & Khademhosseini, 2020; Lee & Gaharwar, 2020).…”
Section: Introductionmentioning
confidence: 99%